Prophylactic Circumferential Retinal Cryopexy to Prevent Pseudophakic Retinal Detachment after Posterior Capsule Rupture during Phacoemulsification. (30th November 2015) - Bertelmann, T.; Heun, C.; Paul, C.; Bari-Kacik, E.; Sekundo, W.; Schulze, S.
Abstract : Purpose . To evaluate whether prophylactic circumferential retinal cryopexy (CRC) can prevent pseudophakic retinal detachment (PRD) development after posterior capsule rupture (PCR) during phacoemulsification. Methods . Retrospective patient chart analysis of eyes experiencing a PCR during phacoemulsification. Comparison of PRD development between eyes receiving CRC (cryo+ group) or not (cryo− group). Results . Overall 106 patients were analyzed, thereof 61 (58%) in the cryo+ and 45 (42%) in the cryo− group. In both clusters a total of 10 PRDs (9.4%) occurred, thereof 3 (30%) in the cryo+ as well as 7 (70%) in the cryo− group( p = 0.087 ), 79.8 ± 81.58 weeks after PCR. Relative/absolute risk reduction in CRC-treated eyes was calculated to be 68%/11%. Prophylactic CRC reduced PRD development 0.3-fold. Number needed to treat was estimated to be 9.4. Conclusion . Prophylactic CRC might be a useful treatment option in eyes with PCR to hamper PRD development in the further course. Further research is indicated to evaluate this beneficial effect between eyes with and without a rupture of the anterior vitreous cortex and accompanying vitreous loss in an expanding number of eyes.